USING MATERNITY WAITING HOME TO PROMOTE EARLY INITIATION OF BREASTFEEDING WITH IN THE FIRST HOUR OF BIRTH IN NIMULE HOSPITAL, MAGWI COUNTY. - Monyajabiri, Delfos Peter; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student's Journal of Health Research Africa, 2025)
Background. Health staff have identified problems with breastfeeding children from 0-6 months especially practicing early initiation of breastfeeding within the first hour of birth in health facilities thus making the need for establishing a Maternity Waiting Home. The aim of this writing was to assess the use maternity waiting home to promote early initiation of breastfeeding within the first hour of birth in Nimule Hospital, Magwi County. Results. At least 78% of mothers of Magwi County breastfed their children within the first hour of birth which was a good practice while 22% of mothers breastfed their children after one hour of birth which was not a good practice. All pregnant women who delivered in the MWH had early initiated breastfeeding within the first hour of birth for 328 newborn babies standing at 100%; Maternal outcomes were good showing that 328 live births stood at 100% and no death stood at 0.0%; Immediate neonatal outcomes have shown 327 live births stands at 99.69% with 3 stillbirths stands at 0.91%; Neonatal outcomes have shown that 325 were discharged stands at 99.08%, 1 died stands at 0.30% and some 3 were referred stands at 0.91%. Conclusion. Outcomes among the MWH for users had contributed to the observed differences. However, many women with high-risk pregnancies did not use MWH for early initiation of breastfeeding indicating a probable gap in awareness of usefulness, or other inability to stay due to other responsibilities at home. Otherwise, the use of MWH could have improved the maternal outcomes in Magwi County especially for early initiation of breastfeeding within the first hour of birth. Recommendation. There is a need to educate mothers and providers on the benefits of the MWH which is the early initiation of breastfeeding with the first hour of birth during the routine ANC.